Performance of semideterminate and indeterminate cowpeas relaycropped into maize in Northeast Nigeria - Kamara, A.Y.; Omoigui, L.O.; Ewansiha, S.U.; Ekeleme, F.; Chikoye, David; Ajeigbe, Hakeem A. (2011)
Field trials were conducted in 2005 and 2006 in Tilla (northern Guinea savanna) and Sabon-Gari (Sudan savanna) in northeast Nigeria to determine the performance of two improved cowpea varieties when relay-intercropped with early and late maize, 6 and 8 weeks after planting the maize. Grain yield, number of branches and number of pods per plant were higher for the variety IT89KD-288 than for IT97K-499-35, whether planted sole or relay-intercropped with maize. Grain yield was lower for IT97K-499-35 than for IT89KD-288 when relay-intercropped with maize irrespective of the maturity period of the companion maize crop. This may be due to the indeterminate growth habit and shade tolerance of IT89KD-288 which allowed a higher pod load than IT97K-499-35. However, relay-intercropping with early maize gave higher yield than relay-intercropping into late maize. Also relay-intercropping at 6 weeks after planting maize (WAP) gave a higher yield than relay-intercropping at 8 WAP. This therefore, suggests that introducing cowpea into short statured early maize may mean less competition for light and soil resources compared to taller late maize. Also introducing the cowpea earlier may allow the crop to make full use of soil moisture during the cropping season.